Hemispheric Asymmetries: The Comparative View - Ocklenburg, Sebastian; Gunturkun, Onur (Frontiers in Psychology, 2012)
Hemispheric asymmetries play an important role in almost all cognitive functions. For more than a century, they were considered to be uniquely human but now an increasing number of findings in all vertebrate classes make it likely that we inherited our asymmetries from common ancestors. Thus, studying animal models could provide unique insights into the mechanisms of lateralization. We outline three such avenues of research by providing an overview of experiments on left-right differences in the connectivity of sensory systems, the embryonic determinants of brain asymmetries, and the genetics of lateralization. All these lines of studies could provide a wealth of insights into our own asymmetries that should and will be exploited by future analyses.